PENDAMPINGAN MASYARAKAT DALAM PENYUSUNAN MASTERPLAN OBJEK WISATA EMBUNG KLEDUNG, KABUPATEN TEMANGGUNG - Ardiana Yuli Puspitasari (Pondasi, 2022)
Embung Kledung is a tourist attraction that utilizes the natural potential of Mount Sumbing and Mount Sindoro so that it is able to offer very beautiful natural scenery accompanied by cool weather. Embung Kledung is located in Kledung Village, Kledung District, Temanggung Regency. Currently the Embung Kledung tourist attraction is managed by the village youth group "Remaja Embung". However, there is still a lot of potential that has not been optimally developed so that more efficient, precise and sustainable development directions are needed. The limited capacity of human resources is a challenge in its development, so assistance is needed in formulating plans for the development of this tourist attraction. The method used is community assistance with a participatory approach. The stages of the activities carried out are licensing, discussion, field observations, preparation of planning documents, and delivery of planning results. The result of this assistance is the compilation of a master plan for the Embung Kledung tourist attraction with the concept of Ecotourism through the assistance of managers to increase capacity and understanding of the process.